Survnvote: a free web based audience response system to support interactivity in the classroom - Ayu, Media Anugerah; Mantoro, Teddy; Habul, Emir; Khasanah, Ana U. (2010)
Survnvote is a free Audience Response System (ARS) for surveys and voting using the web, sms and mobile devices (PDA or smart phone). This paper proposed some improved features of a web-based ARS which replace the clicker with mobile phone and use the web instead of specialist software and infrastructure. Survnvote solved the main problem of traditional ARS which is high cost and need to physically install the receivers in the room. This system offers a more user friendly approach and improved features, e.g. the introduction of crowd management, Survnvote panel that is easy to use, crowd group voting, and several ways to participate in voting. This system gives a better result representation by providing several data formats such as graph, PowerPoint, Excel. Survnvote also provides data analysis to the user. ARS users will experience valuable services by utilizing this system to support interactivity in their classrooms, seminars and conferences. A test-case of the use of this system in a lecture class is provided in this paper.